Implementasi teknologi dalam pemberdayaan kelompok nelayan di Desa Sanur Kauh - Indramanik, Ida Bagus Gede; Sawitri, Ni Putu Yuliana Ria (Nur Science Institute, 2021)
In the village of Sanur Kauh there is a group of fishermen who are currently still operating but have constraints from the processing of group activities carried out, so that this group of fishermen really hope for guidance from universities. Results of observations made by the PKM team from Ngurah Rai University, the fishermen group was very need help to solve the problems they are facing. Fishing group This is the “Ketapang Kembar Fisherman Group” located in Sanur Kauh. Village South Denpasar District, Denpasar City. The problems faced have caused a decrease in the income level of the fishermen coupled with the Covid-19 pandemic condition which also has an impact on decrease in people's purchasing power. These problems will be resolved later with some solutions that will be provided from Ngurah Rai University as an institution education that carries out community service activities. One solution that will given, namely the socialization of processing catches into other products that can be sold to the community and socialization of cooperation to other parties in order to improve income from fishermen.